Polycystic Ovary Syndrome and Hepatic Steatosis: Could Low-Grade Chronic Inflammation Be Mediated by the Spleen?. (January 2013) - Tarantino, G.; Di Somma, C.; Pizza, G.; Brancato, V.; Nedi, V.; Valentino, R.; Orio, F.; Pivonello, C.; Colao, A.; Savastano, S.
Polycystic Ovary Syndrome (PCOS) is characterized by an extreme variety of phenotypes and controversial metabolic implications. Hepatic Steatosis (HS) and low-grade chronic inflammation (LGCI) might be common findings in PCOS. We conducted a cross-sectional study to evaluate the LGCI and HS in young women with PCOS according to their Body Mass index (BMI), Insulin Resistance (IR), and PCOS phenotypes. Sixty young premenopausal PCOS women and 20 age-matched controls participated. Primary outcome measures were the presence/severity of HS; LGCI index evaluated as spleen longitudinal diameter (SLD) by UltraSound, C-Reactive Protein (CRP) and Interleukin (IL)-6 levels; BMI and the Homeostasis Model Assessment (HoMA) of IR. The second outcome measures were testosterone, Sex Hormone-Binding Globulin (SHBG) levels, and Free Androgen Index (FAI). The presence of HS and LGCI was not significantly different between NW and O/O patients, while there were significant differences particularly when the PCOS-women were grouped according to IR or to PCOS phenotypes. At multiple regression adjusted for BMI, HoMA-IR and the spleen size were the major determinants of the severity of HS (β= 0.36, p=0.007, and β= 0.28, p=0.034, respectively). At multiple regression SLD represented the unique predictor of FAI (β=0.32; p=0.018). In young women with PCOS, HS was detected independently from obesity and was well predicted not only by IR but also by spleen size, with variable expression of the liver-spleen axis across the different PCOS subtypes. A possible role of the spleen in determining LGCI also in women with PCOS is emphasized.